Determinan Nilai Perusahaan : (Studi Kasus Pada Perusahaan Teknologi dan Telekomunikasi) - Choirul Ismail Saleh (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
The increase and decrease in company value in 2019-2022 can affect the market price of companies in the technology and telecommunications sectors. Fluctuating company values ​​can make investors think twice about designing their capital. This problem must be handled by the company. Steps that can be taken by companies are to analyze what factors can influence company value. This research aims to determine the influence of liquidity, solvency and profitability ratios on company value (case study of technology and telecommunications companies listed on the IDX in 2019-2022). The research method used is a quantitative method, the data source is secondary data, and the sample collection technique uses a purposive sampling technique. The results of the quantitative analysis show that the liquidity ratio and solvency ratio do not have a significant effect on company value with significant figures of 0.869 and 0.247 > 0.05. Meanwhile, the profitability ratio has a significant effect on company value with a significant figure of 0.000 <0.05. Based on the results of the coefficient of determination (R2), the influence of liquidity, solvency and profitability ratios simultaneously only affects company value by 0.229 or 22.9%, which means 77.1% is influenced by other variables that have not been included in this research.